2022
DOI: 10.1093/hr/uhac229
|View full text |Cite
|
Sign up to set email alerts
|

Targeted approaches to improve tomato fruit taste

Abstract: Tomato (Solanum lycopersicum) is the most valuable fruit and horticultural crop species worldwide. Compared with their progenitors, the fruits of modern tomato cultivars are, however, often described as having unsatisfactory taste or lacking flavor. The flavor of a tomato fruit arises from a complex mix of tastes and volatile metabolites, including sugars, acids, amino acids, and various volatiles. However, considerable differences in fruit flavor occur among tomato varieties, resulting in mixed consumer exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 113 publications
(168 reference statements)
0
9
0
1
Order By: Relevance
“…Similarly, 3-methyl-1-butanol and phenylethyl alcohol were also linked to sweetness in FooDB and may be key volatiles affecting sweetness in ripe tomatoes. A search through the FooDB website revealed that 1-octen-3-ol, benzaldehyde, and benzeneacetaldehyde are known to have a bad taste and that eugenol and guaiacol can underlie bitterness in fruit [ 39 ]. Thus, 1-octen-3-ol, benzaldehyde, benzeneacetaldehyde, eugenol, guaiacol, and nonanal are likely key metabolites underlying the bitter taste of green tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 3-methyl-1-butanol and phenylethyl alcohol were also linked to sweetness in FooDB and may be key volatiles affecting sweetness in ripe tomatoes. A search through the FooDB website revealed that 1-octen-3-ol, benzaldehyde, and benzeneacetaldehyde are known to have a bad taste and that eugenol and guaiacol can underlie bitterness in fruit [ 39 ]. Thus, 1-octen-3-ol, benzaldehyde, benzeneacetaldehyde, eugenol, guaiacol, and nonanal are likely key metabolites underlying the bitter taste of green tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…With an increase in tomato breeding efforts towards better flavor and nutritional quality, there is interest in the use of machine learning models to expedite the breeding process ( Wang et al., 2022 ). A study showed that predictive machine learning models can predict consumer preferences based on the metabolomics of tomato and blueberry lines ( Colantonio et al., 2022 ).…”
Section: Advances In Tomato Flavor Researchmentioning
confidence: 99%
“…Meanwhile, 2-phenylethanol, 5hydroxymethylfurfural, and 6-O-acetylarbutin had higher contents in RF than PF. Of these, 2-phenylethanol is reported to improve the organoleptic properties of cider, offer health benefits through its antioxidant properties [42], and enhance tomato fruit taste [43,44]. In addition to these, 2-(formylamino)benzoic acid, 3,3 ,4-trimethoxyellagic acid, and 6 -Oferuloyl-D-sucrose were solely identified in the RF variety in contrast to the PF variety.…”
Section: Comparison Of Phenolic Compounds Accumulated Differentially ...mentioning
confidence: 99%